Nano-optics and near-field optical microscopy - Zayats, A. V. (Anatoly V.); Richards, David (David R.) (Artech House nanoscale science and engineering series., 2009)
"This groundbreaking book focuses on near-field microscopy which has opened up optical processes at the nanoscale for direct inspection. Further, it explores the emerging area of nano-optics which promises to make possible optical microscopy with true nanometer resolution. This frontline resource helps you achieve high resolution optical imaging of biological species and functional materials. You also find guidance in the imaging of optical device operation and new nanophotonics functionalities"--EBL.